The Effect of Cash Turnover, Receivables Turnover, and Sales Growth on Profitability of Textile and Garment Companies on the IDX (2021-2024) - Luh Arisia Mahatma Dewi; Yoga Adi Prayogi (Equity: Jurnal Akuntansi, 2026)
The economic pressures occurring require textile and garment companies to manage financial performance more effectively to maintain profitability levels. This study aims to analyze the effect of cash turnover, receivables turnover, and sales growth on the profitability of textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2024 period. A quantitative approach was applied in this study with secondary data analyzed through multiple linear regression using SPSS version 27. Sampling using purposive sampling techniques resulted in 56 research samples. The results show that cash turnover and receivables turnover do not have a significant effect on profitability. Conversely, sales growth has a significant effect and is the most dominant factor in increasing profitability. Simultaneously, these three variables have a significant effect on profitability. These findings indicate that increased sales growth is a major factor in driving the financial performance of textile and garment companies.